GROWTH INHIBITION OF CLINICALLY RESISTANT BACTERIA BY MARINE BACTERIA ASSOCIATED WITH SPONGE Aaptos sp. - Duhita S Kencana; Rory A Hutagalung (JOURNAL OF COASTAL DEVELOPMENT, 2008)
The improper and uncontrolled uses of antibiotics against pathogenic bacteria have resulted inthe occurrence of Multi Drugs Resistant (MDR) strains. There is now an urgency to find alternativeantibiotics to combat the MDR strains. Sponge associated microorganisms are among of the mostinteresting and promising marine natural product sources, which produce polyketide and nonribosomal peptide products with various biological activities. In this study, marine bacteria wereisolated from sponge Aaptos sp. collected from North Java Sea, and were screened for antibacterialactivity against MDR strains. Three out of 64 bacterial isolates were successfully screened and werefound to be active against MDR strains, in which 2 isolates (SPA1 and SPA5) were active againstresistant strain Escherichia coli and 1 isolate (SPA21) against resistant strain Proteus sp., respectively.These active isolates were also capable of amplifying NRPS gene fragments necessary for thebiosynthesis of non ribosomal peptides. The identification results revealed that the active isolates areHalomonas aquamarina, Alpha proteobacterium, and Pseudoalteromonas luteviolacea